Microeconomic theory : a heterodox approach - Lee, Frederic S., 1949-2014; Jo, Tae-Hee, 1973- (New York : Routledge, 2018)
"Microeconomic Theory: A Heterodox Approach develops a heterodox economic theory that explains the economy as the social provisioning process at the micro level. Heterodox microeconomics explores the economy with a focus on its constituent parts and their reproduction and recurrence, their integration qua interdependency by non-market and market arrangements and institutions, and how the system works as a whole.This book deals with three theoretical concerns. Due to the significance of the price mechanism to mainstream economics, a theoretical concern of the book is the business enterprise, markets, demand, and pricing. Also, since heterodox economists see private investment, consumption and government expenditures as the principal directors and drivers of economic activity, a second theoretical concern is business decision-making processes regarding investment and production, government expenditure decisions, the financing of investment, the profit mark-up and the wage rate, and taxes. Finally, the third theoretical concern of the book is the delineation of a non-equilibrium disaggregated price-output model of the social provisioning process. This book explores the integration of these various theories with a theoretical model of the economy and how this forms a theory that can be identified as heterodox microeconomics. It will be of interest to both postgraduates and researchers."--Provided by publisher.
Preface -- The making of heterodox microeconomics -- Structure, agency, and modeling the economy -- The business enterprise : structures -- The business enterprise : agency and causal mechanisms -- Markets and demand for the social product -- Competition, the market price, and market governance -- Microeconomics and the social provisioning process -- Appendix 1 Heterodox microeconomics course syllabus -- Appendix 2 Narrative-qualitative-analytical problem sets -- Bibliography -- Index.
Includes bibliographical references (pages 247-266) and index.
Keywords: Microeconomics